PERFORMANCE ANALYSIS OF USAU BATANG TIMPEH IRRIGATION NETWORK MANAGEMENT IN DHARMASRAYA DISTRICT - Darmawan, Tedi; Utama, Lusi; Anif, Bahrul (Rang Teknik Journal, 2025)
Irrigation has a huge impact on meeting water needs for rice fields. Good irrigation needs to pay attention to irrigation management so that it can meet the water needs of the population's rice fields. In this research, the assessment of irrigation management performance is based on five variables, namely physical infrastructure, documentation, personnel, water user farmer associations, and planting productivity. Data collection was carried out by giving questionnaires to water managers and users and the results showed that the irrigation management performance of the Batang Timpeh Usau Irrigation Area was in very poor condition. This condition has an impact on the lack of harvest yields, the lack of farming per year, and the quality of the rice produced being less than optimal. Some improvement efforts that can be carried out include rehabilitating weir buildings, cleaning irrigation channels, assigning special personnel to manage irrigation networks, and providing outreach to the community.